2014
DOI: 10.1523/jneurosci.3192-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Dorsolateral and Ventromedial Prefrontal Cortex Underlie Context-Dependent Stimulus Valuation in Goal-Directed Choice

Abstract: External circumstances and internal bodily states often change and require organisms to flexibly adapt valuation processes to select the optimal action in a given context. Here, we investigate the neurobiology of context-dependent valuation in 22 human subjects using functional magnetic resonance imaging. Subjects made binary choices between visual stimuli with three attributes (shape, color, and pattern) that were associated with monetary values. Context changes required subjects to deviate from the default s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
94
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 30 publications
11
94
2
1
Order By: Relevance
“…Moreover, analysis of interindividual variability revealed that dlPFC-vmPFC interactions during Bonus choices correlated positively with encoding of relative bonus values in vmPFC. Based on this and previous work (Hare et al, 2009), Rudorf and Hare (2014) speculate that the dlPFC sig-nals a context switch to the vmPFC, and initiates a reweighting of stimulus values necessary for context-dependent value maximization, even in situations that lack conflict between competing reward types.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Moreover, analysis of interindividual variability revealed that dlPFC-vmPFC interactions during Bonus choices correlated positively with encoding of relative bonus values in vmPFC. Based on this and previous work (Hare et al, 2009), Rudorf and Hare (2014) speculate that the dlPFC sig-nals a context switch to the vmPFC, and initiates a reweighting of stimulus values necessary for context-dependent value maximization, even in situations that lack conflict between competing reward types.…”
mentioning
confidence: 51%
“…In summary, Rudorf and Hare (2014) provide additional evidence for proposed functions of vmPFC and dlPFC during decisionmaking. Crucially, they demonstrate that interactions between the dlPFC and vmPFC play a role in context-dependent, value-based choice, even in the absence of conflicting reward outcomes.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…it appears that these circuits constitute distinct control systems that can compete with or influence the activity of the (a)-(c) circuits. For example, purposefully focusing one's attention on the healthiness of food options can affect one's eating choices, and this effect appears to be mediated by activity in the dlPFC modulating activity in the vmPFC (Hare, Malmaud, & rangel 2011;see also Baumgartner, Knoch, Hotz, eisenegger, & Fehr 2011;Botvinick & Braver 2015;Hare et al 2009;Hutcherson, Plassmann, Gross, & rangel 2012;Ocshner & Gross 2005;Plassmann, O'Doherty, Shiv, & rangel 2008;rudorf & Hare 2014;Shenhav et al 2013;Sokol-Hessner, Hutcherson, Hare, & rangel 2012). These changes can also be broadcast back to (a) and (b) circuitry, thereby influencing one's motivation (Pujara & Koenigs 2014).…”
Section: Extending the Account To Normative Judgmentmentioning
confidence: 99%